1994
DOI: 10.2166/nh.1994.0004
|View full text |Cite
|
Sign up to set email alerts
|

Metal Transport in Groundwater Contaminated by Acid Mine Drainage

Abstract: Acid mine drainage from a rock dump at an abandoned mine in Dalarna, Sweden, has contaminated the groundwater and created a leachate plume characterized by low pH and high concentrations of Fe, SO4, and heavy metals. Groundwater samples have been collected in order to explain the observed spatial variations in groundwater chemistry. The mineralogy of soil samples collected at the water table has been identified by X-ray diffraction analysis In order to determine which processes may be controlling the evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…Previous mineral equilibria studies (Herbert 1994(Herbert , 1995a(Herbert , 1995b, using geochemical conditions observed near well B1 (Table 1), have concluded that goethite is the most stable secondary Fe mineral forming in the groundwater. Lepidocrocite reaches saturation in the groundwater only during snowmelt when groundwater pH increases (Herbert 1995b).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous mineral equilibria studies (Herbert 1994(Herbert , 1995a(Herbert , 1995b, using geochemical conditions observed near well B1 (Table 1), have concluded that goethite is the most stable secondary Fe mineral forming in the groundwater. Lepidocrocite reaches saturation in the groundwater only during snowmelt when groundwater pH increases (Herbert 1995b).…”
Section: Discussionmentioning
confidence: 91%
“…The glacial till has developed from the gneissic bedrock, and it is consequently noncalcareous with a low acid neutralization capacity. Groundwater occurs in the unconfined till unit, and has been investigated in geochemical studies by Herbert (1994Herbert ( , 1995b. The studies indicate that the atmospheric oxidation of primarily pyrite (FeS2) and pyrrhotite (Fe7S8), along with the percolation of water through the unsaturated rock dump, has led to the contamination of the groundwater.…”
Section: Field Site and Samplingmentioning
confidence: 99%
“…However, the metal concentrations were low related to leachates from other acid mine areas (e.g. [25,26]). Wastewater was collected from the KM laundry in Gammelstad after washing of overalls used by mine workers from LKAB in 1995.…”
Section: Wastewatermentioning
confidence: 92%
“…However, as copper may also adsorb on, for example, goetite, which may be continuously formed at the prevailing p H conditions, new sites would become available. Third, copper may substitute for iron in, for example, goetite leading to coprecipitation [Herbert, 1994]. To distinguish and discriminate among these processes is a delicate task, as they may yield quite similar results with regard to limiting copper leaching at neutral p H.…”
Section: Precipitation/dissolution Of Secondary Mineralsmentioning
confidence: 99%